2016
DOI: 10.1002/dev.21440
|View full text |Cite
|
Sign up to set email alerts
|

Maternal deprivation alters growth, food intake, and neuropeptide Y in the hypothalamus of adolescent male and female rats

Abstract: Maternal deprivation (MD) for 24 hr during the neonatal period impairs body weight gain in adolescent and adult rats. It has been previously shown that maternally deprived rats consume less standard and carbohydrate-rich diets. Because neuropeptide Y (NPY) is implicated in feeding behavior, we assessed, prospectively, the effects of maternal deprivation, imposed on postnatal days (PND) 3 (DEP3) or 11 (DEP11), on physical development (snout-anal length and body weight gain, measured once a week) and food intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…In the present study, we tested the impact of maternal deprivation imposed in two moments of the neonatal development, immediately before (DEP3) and in the midst of the SHRP (DEP11), on physiological variables, such as body weight gain and relative adrenal weight, and on emotional behavior and NPY-ir in the BLA, vHPC, and dHPC of male and female rats. Impairment of body weight gain replicated previous findings ( Wertheimer et al, 2016 ), and in the present study, we also found that females, regardless of their infancy history, showed heavier adrenals than their male counterparts; in addition, maternal deprivation on PND 3 resulted in the heaviest adrenal weights both in males and females, suggesting that DEP3 adolescents may be under chronic stress ( Jankord et al, 2011 ). There was a clear distinctive age-dependent effect of maternal deprivation on emotional behavior, inasmuch as DEP3 adolescents of both sexes displayed the highest anxiety index and the greatest frequency of immobility in the FST; DEP11 adolescents, in turn, displayed more immobility than their CTL counterparts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we tested the impact of maternal deprivation imposed in two moments of the neonatal development, immediately before (DEP3) and in the midst of the SHRP (DEP11), on physiological variables, such as body weight gain and relative adrenal weight, and on emotional behavior and NPY-ir in the BLA, vHPC, and dHPC of male and female rats. Impairment of body weight gain replicated previous findings ( Wertheimer et al, 2016 ), and in the present study, we also found that females, regardless of their infancy history, showed heavier adrenals than their male counterparts; in addition, maternal deprivation on PND 3 resulted in the heaviest adrenal weights both in males and females, suggesting that DEP3 adolescents may be under chronic stress ( Jankord et al, 2011 ). There was a clear distinctive age-dependent effect of maternal deprivation on emotional behavior, inasmuch as DEP3 adolescents of both sexes displayed the highest anxiety index and the greatest frequency of immobility in the FST; DEP11 adolescents, in turn, displayed more immobility than their CTL counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Twenty-eight litters were distributed in CTL (nine litters), DEP3 (10 litters), and DEP11 (nine litters). In each litter, two males and two females were tested in the elevated plus maze, whereas the remainder of the litter was not tested and provided baseline values of parameters published previously ( Wertheimer et al, 2016 ) and NPY-ir.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of MD on prepulse inhibition were replicated by Husum and Mathé, who also showed that DEP9 male rats exhibited lower levels of neuropeptide Y (NPY) in the occipital cortex and hippocampus; whether or not the changes in prepulse inhibition and NPY are related still needs clarification, although this could be a possibility because dopamine negatively regulates NPY levels. NPY levels were also shown to be reduced in the hypothalamus, as well as in the amygdala and hippocampus (unpublished data, A. S. Miragaia, G. S. Wertheimer, A. C. Consoli, R. Cabbia, B. M. Longo, C. E. Girardi, D. Suchecki) of male and female DEP3 and DEP11 rats. Therefore, the NPY system may be a particularly interesting endpoint worthy of investigation, giving its involvement with mood and anxiety disorders …”
Section: Consequences Of Disruption Of the Mother‐infant Relationshipmentioning
confidence: 90%
“…In the amygdala, early-life stress increased NPY mRNA levels at 30 days postnatally in females, only [ 126 ]. When examined as adolescents, early-life stress decreased NPY neuron density in the arcuate nucleus equally in both sexes, as compared to unstressed controls [ 127 ]. However, when animals exposed to early-life stress were examined in adolescence, females tended to exhibit lower NPY expression in specific brain regions.…”
Section: Sex Differences In Brain-specific and Peripheral Npy Exprmentioning
confidence: 99%